TEAM to defeat COVID-19: A management strategy plan to address return to play in sports medicine - Santos-Ferreira, D.; Tomás, R.; Dores, H. (Orthopaedic Journal of Sports Medicine, 2020)
A new viral disease named COVID-19 spread rapidly into a pandemic in early 2020. Most countries have active community transmission and imposed measures such as social distancing and travel restrictions to mitigate its effect. Many sporting events all over the globe were canceled or postponed. In this article, we briefly discuss some important topics regarding the COVID-19 pandemic and propose a strategy to manage return to play in professional athletes. We searched the PubMed and Google Scholar databases to identify articles published through May 12, 2020, using the following keywords: "coronavirus," "COVID-19," "SARS-CoV-2," "athlete," and "return to play." Although athletes have a lower risk of severe disease, preventive measures are still very important for minimizing time away from training, avoiding potential complications, slowing the pandemic spread, and ultimately protecting the health of those with a higher risk of complications and death. Athletes may present with mild disease, but complications such as pulmonary fibrosis and myocardial injuries have to be considered. Although still controversial, athletes should be evaluated before return to play and monitored accordingly afterward via proper clinical assessments and testing.